1997
DOI: 10.1046/j.1423-0410.1997.7240238.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Alloimmunization after Transfusion

Abstract: There was a low incidence of platelet-specific antibodies after one series of blood transfusions in this group of patients. This is similar to the results of some previous studies in multiply transfused patients, but not with those of others who found a higher incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…HLA antibody formation after a single blood transfusion event has not been extensively studied and percentages ranging from 15 to 95 percent are reported in literature, depending on the test method used, the timing of testing, and the blood component transfused. 15,17,18 Fauchet and coworkers 15 found an alloimmunization rate of 33.6 and 64.3 percent in male and female cardiac surgery patients, respectively, when tested 8 and 15 days after receiving RBCs transfusions and FFP infusions. Gleichmann and Breininger 17 reported 74 percent cytotoxic antibodies, with a peak 2 weeks after transfusion, in open heart surgery patients after a single massive blood transfusion event with whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…HLA antibody formation after a single blood transfusion event has not been extensively studied and percentages ranging from 15 to 95 percent are reported in literature, depending on the test method used, the timing of testing, and the blood component transfused. 15,17,18 Fauchet and coworkers 15 found an alloimmunization rate of 33.6 and 64.3 percent in male and female cardiac surgery patients, respectively, when tested 8 and 15 days after receiving RBCs transfusions and FFP infusions. Gleichmann and Breininger 17 reported 74 percent cytotoxic antibodies, with a peak 2 weeks after transfusion, in open heart surgery patients after a single massive blood transfusion event with whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a high degree of uncertainty about the magnitude of the problem created by platelet‐specific antibodies. Thus, while for some authors platelet‐specific antibodies constitute a frequent finding in multiply transfused patients, with prevalence rates ranging from 15 percent to 36 percent, 2–4 for others, such antibodies are much less frequent, appearing in only 0 to 9 percent 5–8 of these patients.…”
mentioning
confidence: 99%
“…Fauchet et al . [15] in a previous study demonstrated HLA prevalence of 45·7% for cardiac patients transfused with non‐leucocyte‐depleted red cells while other authors [16,23] demonstrated lower prevalence (12–15%) when using buffy‐coat‐depleted or filtered red cells.…”
Section: Discussionmentioning
confidence: 98%